Prognostic implications of and audiometric evidence for hearing fluctuation in Meniere's disease. (7th September 2015) - Hoa, Michael; Friedman, Rick A.; Fisher, Laurel M.; Derebery, M. Jennifer
Abstract : Objectives/Hypothesis: 1) To establish criteria for significant hearing fluctuation by assessing the range and occurrence of hearing fluctuations over the course of Meniere's disease; 2) to determine if audiometric evidence exists to support the notion that Meniere's disease is a pathophysiologic process involving the whole cochlea; and 3) to suggest prognostic implications for initial hearing fluctuation in patients with Meniere's disease. Study Design: Retrospective case series review. Methods: A total of 488 patients diagnosed by 1995 American Academy of Otolaryngology–Head and Neck Surgery Meniere's disease criteria for whom audiometric data were prospectively collected (2 cohorts: 341 and 146 patients initially seen between April 2002 to July 2003 and between January to December 2010, respectively). Based on several definitions for significant hearing fluctuation, change in hearing was categorized as "same, " "worse, " or "better" between any two consecutive evaluations. The relationship of initial hearing fluctuation to future hearing fluctuation and future hearing loss was evaluated. Results: Hearing fluctuation was evident in Meniere's disease patients with heterogeneous audiometric follow‐up; and the characteristics of these hearing fluctuations, including the mean incidence, is described. Audiometric data suggests that there is a high congruence in Meniere's disease between changes in low‐ and high‐frequency thresholds. Initial hearing fluctuation is associated with the occurrence of future and more frequent hearing fluctuations. Conclusion: Understanding the range of hearing fluctuations establishes a basis for determining audiometric thresholds used in evaluating future therapeutic trials aimed at the prevention of hearing loss in Meniere's disease. This knowledge will also inform the counseling directed toward patients diagnosed with Meniere's disease. Level of Evidence: 4. Laryngoscope, 125:S1–S12, 2015